Fører endringer i loven til endringer i rettspraksis? - Synøve N. Andersen; Morten Holmboe; Torbjørn Skardhamar (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract On June 25, 2010, sentencing for certain violent crimes should have increased substantially in Norway due to changes in the Criminal Act and the explicit intention of lawmakers. But did this actually happen? In this paper, we compare sentencing practices before and after the penal reform using administrative registry data from all Norwegian courts on persons convicted for bodily harm and/or assault. Results from regression discontinuity analyses show that despite clear incentives to increase sentences for violent offences, there were no statistically significant changes in the length of sentences imposed following the penal reform. This highlights the importance of conducting empirical assessments of the impact of penal changes on judicial behaviour and other aspects of the criminal justice system.